Effect of Vermicompost on Growth, Essential Oil, and Health of Thymus Vulgaris. Issue 3 (3rd July 2017) - Amooaghaie, Rayhaneh; Golmohammadi, Shahrzad
ABSTRACT: In this study, the effect of various vermicompost substitutions (0, 25, 50, and 75%) was investigated on germination, growth and development, photosynthetic parameters, the essential oil content, and disease resistance of Thymus vulgaris . Results showed that 25% vermicompost substitution promoted the best seedling emergence indices, whereas maximum length, fresh and dry weight of aerial parts and root, chlorophyll and carotenoid contents, photosynthetic efficiency, and the highest essential oil content were observed in 50% vermicompost substitution. Vermicompost was an effective biocontrol agent against Fusarium oxysporum and Phytophthora infestans . Suppression of pathogens by vermicompost was enhanced progressively with increasing rates of substitution of vermicompost, and the highest suppression obtained in 75% vermicompost substitution. The disease protection correlated to development of activities of defense-related enzymes including β-1, 3-glucanase, phenylalanine ammonialyase, polyphenol oxidase and peroxidase, and total phenolics content. These results suggest the potential of vermicompost in promoting of plant yield as well as inducing systemic resistance in Thymus vulgaris .